2015
DOI: 10.1371/journal.pone.0133477
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous Meningitis in Children and Adults: A 10-Year Retrospective Comparative Analysis

Abstract: BackgroundTuberculous meningitis (TBM) is the most lethal form of Mycobacterium tuberculosis infection, which has a high rate of neurological complications and sequelae.ObjectivesOur study offers a real-world infectious disease clinic perspective, being thus representative for the clinical environment of developing countries.MethodsWe performed a retrospective analysis of the 127 adult and 77 pediatric cases diagnosed with TBM in the Infectious Disease Hospital of the School of Medicine of Iasi, Romania betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
32
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 20 publications
12
32
2
3
Order By: Relevance
“…Among the extrapulmonary tuberculosis TB Meningitis has a higher incidence (Tanden et al 1970). [11] Onset: In the present study, the onset is acute in 28% and subacute in 32% and insidious in 40% in adults. (Udani PK 1970).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Among the extrapulmonary tuberculosis TB Meningitis has a higher incidence (Tanden et al 1970). [11] Onset: In the present study, the onset is acute in 28% and subacute in 32% and insidious in 40% in adults. (Udani PK 1970).…”
Section: Discussionsupporting
confidence: 46%
“…Tandon et al (1970) has the access rate varied from 5% to 15%. [11] CT scan was taken for all the patients. 8 patients had showed thick basilar exudates which appear as intensely enhancing area in the basal cistern.…”
Section: Discussionmentioning
confidence: 99%
“…Miftode et al reported TBM Grade II in 68% of patients. [8] Almost onethird of patients (33.3%) had active TB on chest X-ray. On cranial CT or MRI, 28.2% of patients had hydrocephalus, 7.6% tuberculoma, and 5.1% had spinal arachnoiditis presenting as paraparesis.…”
Section: Discussionmentioning
confidence: 99%
“…Most of TBM cases are diagnosed in advanced stages due to its vague presentation in the early phase (5), misinterpretation of disease by physicians, patient's low socioeconomic condition, and sometimes rapid progression of TBM (6).…”
Section: Introductionmentioning
confidence: 99%